The moderation role of sales promotion on perspected value and price on repurchase intention by mediation of dunkin donat customer satisfaction - Sulasri Bintang Kerti; Surya Bintarti; Sri Wahyuningsih (Junal Ilmu Manajemen, 2023)
Western culture has entered Indonesia, not only in clothing and fashion, but in all areas including food. Rice which is the main food of Indonesian people has now been replaced with wheat. This study aims to examine and find the relationship between perceived value and price on repurchase intention through mediation of consumer satisfaction moderated by sales promotions. The number of respondents in this study amounted to 104 respondents with the characteristics of respondents who had consumed and purchased Dunkin Donuts in the Bekasi Regency area. The taking of this population is non-probability sampling and the technique of taking respondents is purposive. This research was processed using a regression technique, which was processed using SmartPLS 4 Software. This research proves: 1) The perceived value of Dunkin Donuts consumers can encourage repurchase intentions on Dunkin Donuts products. 2) Pricing of Dunkin Donuts products cannot encourage consumers to repurchase. 3) Dunkin Donuts consumer satisfaction can mediate perceived value to encourage consumers to repurchase. 4) Consumer satisfaction is sufficient to mediate the prices set for Dunkin Donuts products on the repurchase intention of Dunkin Donuts consumers. 5) A high level of consumer satisfaction can encourage consumer intentions to repurchase. 6) Sales promotion can play a role in strengthening the perceived value of Dunkin Donuts consumers' repurchase intention. 7) Sales promotion has a direct role on repurchase intention so that it cannot strengthen the price relationship on repurchase intention.